Development and validation of the patient centeredness index for primary care. Issue 23 (3rd January 2022) - Rose, Gail L.; Bonnell, Levi N.; O'Rourke‐Lavoie, Jennifer B.; van Eeghen, Constance; Reynolds, Paula; Pomeroy, Doug; Clifton, Jessica; Scholle, Sarah Hudson; Natkin, Lisa W.; Callas, Peter; Hitt, Juvena R.; Crocker, Abigail M.; et al.
Abstract: Aims and Objectives: To describe the development of the Patient Centeredness Index (PCI), evaluate its psychometric characteristics and evaluate the relationships between scores on the PCI and an established measure of empathy. Background: Patient centeredness helps patients manage multiple chronic conditions with their providers, nurses and other team members. However, no instrument exists for evaluating patient centeredness within primary care practices treating this population. Design: Multi‐site instrument development and validation. STROBE reporting guidelines were followed. Methods: To identify themes, we consulted literature on patient centeredness and engaged stakeholders who had or were caring for people with multiple chronic conditions ( n  = 7). We composed and refined items to represent those themes with input from clinicians and researchers. To evaluate reliability and convergent validity, we administered surveys to participants ( n  = 3622) with chronic conditions recruited from 44 primary care practices for a large‐scale cluster randomised clinical trial of the effects of a practice‐level intervention on patient and practice‐level outcomes. Participants chose to complete the 16‐item survey online, on paper or by phone. Surveys assessed demographics, number of chronic conditions and ratings of provider empathy. We conducted exploratory factor analysis to model the interrelationships among items. Results: A single factor explained 93% of total variance. Factor loadings ranged from 0.55–0.85, and item‐test correlations were ≥.67. Cronbach's alpha was .93. A moderate, linear correlation with ratings of provider's empathy ( r  = .65) supports convergent validity. Conclusions: The PCI is a new tool for obtaining patient perceptions of the patient centeredness of their primary care practice. The PCI shows acceptable reliability and evidence of convergent validity among patients managing chronic conditions. Relevance to clinical practice: The PCI rapidly identifies patients' perspectives on patient centeredness of their practice, making it ideal for administration in busy primary care settings that aim to efficiently address patient‐identified needs. Trial registration: Clinicaltrials.org Protocol ID: WLPS‐1409‐24372. Title: Integrating Behavioural Health and Primary Care for Comorbid Behavioural and Medical Problems (IBHPC).